Implementasi House of Risk dalam Strategi Mitigasi Penyebab Risiko pada Aktivitas di Bagian Produksi PT. XYZ - Octavia, Chendrasari W.; Magdalena, Riana; Prasetya, Wibawa (Metris: Jurnal Sains dan Teknologi, 2019)
In the current competitive environment, every company is required to have a strong supply chain network as part of the company's strategy to survive in the company environment. However, the establishment of a strong supply chain network is not a guarantee of risk free. Risk is the impact of an event, an event occurs due to uncertainty that cannot be predicted by stakeholders. In this study aims to identify and map risk events and causes of risk, and provide proposed actions to minimize risk mitigation strategies with the House of Risk approach. The House of Risk approach is part of risk management in the supply chain where this method is able to identify and map risks and events of risk, and provide proposed mitigation strategies. The results of this study obtained 10 risk events and 17 risk causes with the proposed mitigation actions 7 actions.